A multi-responsive system based on intramolecular B ← OP Lewis acid–base pairs. Issue 30 (21st July 2022) - Wang, Yu; Liu, Kanglei; Chen, Pangkuan; Yin, Xiaodong; Peng, Tai; Iqbal, Javed; Wang, Nan
Abstract : Novel intramolecular B ← OP compounds were synthesized, which can exhibit multi-stimuli responsive properties upon tuning the dynamic B–O bond strength. Abstract : A series of amino-triarylborane based flexible Lewis pairs with P(O)R2 (R = phenyl, methylphenyl) and BR2 (R = 2, 4, 6-trimethylphenyl (Mes), 2, 6-dimethyl-4-methoxyphenyl (Mes(OMe)) were synthesized and fully characterized. These compounds display distinct responses toward multiple external stimuli including solvent, temperature and pressure. A detailed study shows that the ability of reversible switching between the open and closed structures based on the intramolecular B ← O bond plays a key role in their solution state fluorescence response to external stimuli, which can be further tuned by adjusting the electronic/steric properties of the substituents on the BR2 /P(O)R2 unit. All these compounds exhibit remarkable mechanochromism. Furthermore, upon grinding, pressure-induced blue-shifted and red-shifted emissions were observed for B2 /B3 and B1 /B4, respectively. This solid state emission change is fully reversible for B2–B4 upon exposure to vapours of several common solvents.